Karl Barth in Sino-Christian Theology - ZHENG, Jialu (Journal of Research for Christianity in China (JRCC), 2025)
The essay firstly focused on the concept—“Sino-Christian”, when it began and how it came from, then described the main ideas of theologian Karl Barth. Finally, a summary about the recently research output of Karl Barth in Sino-Christian theology was made to show the outline and the future of the Karl Barth studying. To deal with the great “church doctor” Karl Barth is a necessary approach for Sino-Christian theology to get rid of the critics from the church in China. Since the theology of Karl Barth basically stands on the land of church dogmatic, and has strong influence on the church life, to understand and communicate with the church and Christians in China, it is better to accept and understand the way how the church talks, rather than change the Christian with philosophy or culture. Moreover it is not only an academic consideration, but an actual concern.